An Interval-Parameter Fuzzy Linear Programming Approach for Accounting and Planning of Energy-Environmental Management Systems - Dong, Cong; Huang, Guohe; Cai, Yanpeng; Yue, Wencong; Rong, Qiangqiang (Journal of Environmental Accounting and Management, 2026)
In this paper, an energy systems planning (ESPM) model was developed for supporting the planning of an energy management system where the environmental protection was considered under uncertainty. This model was solved based on the interval-parameter fuzzy linear programming, which incorporated the fuzzy linear programming and interval-parameter linear programming into a general optimization framework. Through the conduction of this study, (a) complexities regarding energy activities and environmental conservation in energy management systems could be identified and analyzed, (b) uncertainties of parameters in energy man-agement systems could be incorporated into the planning process on the basis of interval numbers and fuzzy sets, (c) the interval form solutions could enhance the adaptation of ESPM to uncertain conditions, (d) the trade-off between energy activities and environmental protection measures as well as that between optimality and reliability of energy sys- tems couldbe reflected through the introduction of satisfaction degrees, and (e) desirable cost-minimized schemes for energy activitiessuch as energy resources allocation, technological development, facility capacity expansion and pollutant emission control could be provided for decision makers.